2022
DOI: 10.3390/electronics11030431
|View full text |Cite
|
Sign up to set email alerts
|

Change Detection in Remote Sensing Image Data Comparing Algebraic and Machine Learning Methods

Abstract: Remote sensing technology has penetrated all the natural resource segments as it provides precise information in an image mode. Remote sensing satellites are currently the fastest-growing source of geographic area information. With the continuous change in the earth’s surface and the wide application of remote sensing, change detection is very useful for monitoring environmental and human needs. So, it is necessary to develop automatic change detection techniques to improve the quality and reduce the time requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The proposed ANPC technique has also shown improved accuracy compared with other stated algorithms in the literature. Goswami et al [44] implemented a change detection technique for a multitemporal image with 91% accuracy, which is lesser than the proposed method and can detect fewer spectral bands only. Zhu et al [45] implemented continuous change detection and classification (CCDC) algorithm using a multispectral dataset and achieved an accuracy of 90%, which is less than the proposed technique and not applicable to higher resolution datasets, which is a part of the pre-classification technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed ANPC technique has also shown improved accuracy compared with other stated algorithms in the literature. Goswami et al [44] implemented a change detection technique for a multitemporal image with 91% accuracy, which is lesser than the proposed method and can detect fewer spectral bands only. Zhu et al [45] implemented continuous change detection and classification (CCDC) algorithm using a multispectral dataset and achieved an accuracy of 90%, which is less than the proposed technique and not applicable to higher resolution datasets, which is a part of the pre-classification technique.…”
Section: Resultsmentioning
confidence: 99%
“…Various authors have reported the work done over LULC using different change detection techniques. Goswami et al [44] implemented a change detection technique for multitemporal images. The decision tree algorithm with the PCC technique is proposed and compared with other change detection techniques, such as image differencing using a multispectral dataset.…”
Section: Introductionmentioning
confidence: 99%
“…The suggested system was tested on the ISCX botnet dataset, and the findings show that it works, with F-1 varying from 0.923 to 0.96, employing standard Machine-Learning techniques. Furthermore, employing an 80:20 train-test split and 10-fold cross-validation, the Extra Trees model [35] achieved up to 97.5 percent overall accuracy and 96 percent overall accuracy.…”
Section: Image Analysis-based Methodsmentioning
confidence: 99%
“…We chose a quantitative approach of comparing raster pairs. Specifically, the classification-based change detection method [30,31] was used for this purpose. However, before comparing classification results, a sieve filter was run on each classified raster to remove isolated and obviously misclassified pixels or pixel chunks, as similar works suggest [32].…”
Section: Post-processingmentioning
confidence: 99%